Associated factors with the academic use of social networks in medical students from 40 cities in Latin America - Valladares-Garrido, Mario J. (2020)
Aim: To identify the factors associated with the academic use of social networks in medical students from 40 faculties in Latin America. Methods: Analytical, cross-sectional analysis of secondary data in medical students from 40 Latin American cities. A self-administered questionnaire was used to evaluate the academic use of social networks and their association with socio-educational characteristics and training in scientific databases. Mixed effects multilevel generalized linear models (MEGLM) were used to estimate prevalence ratios (PR). Results: Of 11587 participants, 57.7% used social networks academically. The level of advanced English increased 1.33 times the prevalence of academic use of social networks (PR: 1.33, 95% CI: 1.24-1.43, p <0.001) while belonging to more than one academic-scientific extracurricular group decreased 34% said prevalence (PR: 0.66, 95% CI: 0.54-0.81, p <0.001). The training for SciELO and Google Scholar increased 18% (PR: 1.18, CI95%: 1.11-1.25, p <0.001) and 11% (PR: 1.11, CI95%: 1.05-1.18, p <0.001) the prevalence of use of social networks in an academic way, respectively. Conclusion: We can affirm that, more than half of the respondents use social networks in their medical training. Proceeding from seven out of eleven surveyed countries, reporting basic-advanced English level, being trained in SciELO and Google Scholar were positively associated with using social networks academically. On the contrary, coming from a private university, belonging to extracurricular groups and not being able to use Google Scholar was associated negatively.